2002
DOI: 10.1021/jm020979u
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Long-Chain Carbamoyl Aminocarnitine Derivative, a Reversible Carnitine Palmitoyltransferase Inhibitor with Antiketotic and Antidiabetic Activity

Abstract: The synthesis and pharmacological activity of reversible CPT I inhibitors as potential antiketotic and antidiabetic drugs are reported. Such inhibitors constitute a series of enantiomerically pure aminocarnitine derivatives having the general formula (CH3)3N+CH2CH(ZR)CH2COO- (with Z = ureido, carbamate, sulfonamide, and sulfamide moieties; R = C7-C14 linear alkyl chains). A primary pharmacological screening based on the evaluation of CPT I activity in intact rat liver (L-CPT I) mitochondria revealed the best a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 24 publications
1
38
0
2
Order By: Relevance
“…Another compound we tested in experimental diabetes, an ureidic derivative from class of "carnitine analogues with long alkyl chain". This ureidic compound, with extraordinarily high selectivity toward the liver CPT1 isoform with respect to the heart isoform was able to reduce serum glucose levels in diabetic db/db mice treated orally for 45 days at a dose of 50 mg/kg twice a day, showing also an antiketotic activity in normal fasted rats and therefore selected for development as a potential antiketotic and antidiabetic drug [13].…”
Section: Current Research In Diabetes and Obesity Journalmentioning
confidence: 99%
“…Another compound we tested in experimental diabetes, an ureidic derivative from class of "carnitine analogues with long alkyl chain". This ureidic compound, with extraordinarily high selectivity toward the liver CPT1 isoform with respect to the heart isoform was able to reduce serum glucose levels in diabetic db/db mice treated orally for 45 days at a dose of 50 mg/kg twice a day, showing also an antiketotic activity in normal fasted rats and therefore selected for development as a potential antiketotic and antidiabetic drug [13].…”
Section: Current Research In Diabetes and Obesity Journalmentioning
confidence: 99%
“…ST1326 was initially selected by Sigma-Tau laboratories as a candidate for diabetes and ketoacidosis therapy. 13,14 Results reported by Pacilli et al 15 demonstrated that the pharmacologic inhibition of FAO by ST1326 impairs cancer cell survival and inhibits tumor cell proliferation in in vitro and in vivo models of Burkitt lymphoma. Therefore, in this study we aimed to expand this approach, investigating the in vitro antileukemic activity of ST1326 on human leukemia cell lines and primary cells obtained from patients with different hematologic diseases.…”
Section: Introductionmentioning
confidence: 97%
“…A reversible CPT1A inhibitor, (R)-N-(tetradecylcarbamoyl)-aminocarnitine (ST1326) developed initially for diabetes treatment (6,7), was shown to decrease lymphoma (8) and leukemia (9) cell growth in preclinical studies. Though, no information is available on its effects to activated/proliferating CLL cells.…”
mentioning
confidence: 99%